ROTIFERS, THEIR DISTRIBUTION, ABUNDANCE AND SEASONAL VARIATION IN CHILIKA LAGOON - MUKHERJEE, M.; BANIK, S. K.; SURESH, V. R.; SHARMA, A. P. (Journal of the Inland Fisheries Society of India, 2020)
The distribution, diversity, abundance of rotifers and influence of environmental variables on them in Chilika lagoon have been studied. Twenty three species of rotifers, unreported earlier from Chilika, have been identified. Members of the family Brachionidae were most abundant in the lagoon. Northern sector of the lagoon was most diverse and southern sector was the least. Bray-Curtis similarity and PCA showed distinct seasonal difference in distribution and abundance. Salinity, transparency, silicate and total hardness were the most critical environmental parameters influencing rotifers in the lagoon.Key words: Rotifers, Chilika lagoon, distribution, Canonical analysis